Opportunities in agriculture and forestry to mitigate greenhouse gases: results of a scientific consultation - Dumanski, Julian; von Grebmer, Klaus; Pieri, Christian J. (1998)
Experts agree that the doubling of atmospheric concentrations of the greenhouse gas carbon dioxide seems to be inevitable. There is an urgent need for off-the-shelf solutions to bridge the next 30 50 years until new technologies will be broadly available. Agriculture, forestry and agro-forestry present some good opportunities: sequestering atmospheric carbon through state-of-the-art agriculture, forestry and agro-forestry could help to buy time which is urgently needed. This contribution could be done under classic win-win conditions, as these systems enhance soil organic matter and improve land quality, while concurrently contributing to improved global environmental conditions. Initial partnerships between large multilateral institutions such as the World Bank and the Global Environmental Facility (GEF), farmer associations, the private sector and the public sector could speed up the global adoption and implementation process. The carbon trading credits established under the Kyoto Protocol do encourage such partnerships."